2013
DOI: 10.1111/hel.12039
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for the “screen and treat” Strategy of Helicobacter pylori to Prevent Gastric Cancer in Healthy Korean Populations

Abstract: Individuals preferred to take the "screen and treat" strategy for the prevention of gastric cancer. Further intervention study is warranted to see if implementation of decisional support would improve decision quality and patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 37 publications
4
24
1
Order By: Relevance
“…Of the nine studies included in this review, two were conducted in eastern China (11, 12), two in South Korea (13, 14), two in North America (15, 16), and one each in Ethiopia (17), India (18), and Malaysia (19). All studies focused on populations at increased risk for gastric cancer, except the US population-based survey to assess and promote awareness (15).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the nine studies included in this review, two were conducted in eastern China (11, 12), two in South Korea (13, 14), two in North America (15, 16), and one each in Ethiopia (17), India (18), and Malaysia (19). All studies focused on populations at increased risk for gastric cancer, except the US population-based survey to assess and promote awareness (15).…”
Section: Resultsmentioning
confidence: 99%
“…When asked how people can acquire the infection, only 26% of participants mentioned water (16). When asked whether oral transmission was usual among family members, 31.1% of participants responded “yes,” 12.6% responded “no,” and 49.5% responded “do not know” (14). When asked about transmission, people who tested positive for H. pylori showed less understanding than those who tested negative (12).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that long-term infection with Hp in patients is an important risk factor for gastric cancer (Adamsson et al, 2013). In 1994, the World Health Organization Cancer Center categorized Hp into the first class of carcinogens (Shin et al, 2013). The incidence of gastric cancer has been steadily increasing.…”
Section: Introductionmentioning
confidence: 99%